2020
DOI: 10.1155/2020/8848116
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic and Mechanical Relationship of Individual Fracture in Rock under Compression and Shearing: Theoretical Study

Abstract: In this paper, a new approach has been developed for predicting the hydraulic and mechanical relationship of individual fractures subjected to normal stress and compression-shear stress. Considering that the closure process of rough fracture subjected to normal stress can be divided into two phases (linear behavior and nonlinear behavior), a relationship between normal stress and fracture aperture is derived through the minimum potential energy principle. Then, a formulation for calculating fracture permeabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Xiong et al [12] conducted laboratory and numerical shear-flow coupling tests to establish the relationship between hydraulic conductivity and mechanical aperture. Zhou et al [13] considered the dilation effect caused by normal stress and shear stress and derived a theoretical analytical equation for fracture permeability in the shear process. Shen et al [14] concluded that the fracture transmissivity increases continuously with 2 Geofluids shear displacement before the peak shear strength and is essentially constant after the peak shear strength when the effective normal stress is greater than 10 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…Xiong et al [12] conducted laboratory and numerical shear-flow coupling tests to establish the relationship between hydraulic conductivity and mechanical aperture. Zhou et al [13] considered the dilation effect caused by normal stress and shear stress and derived a theoretical analytical equation for fracture permeability in the shear process. Shen et al [14] concluded that the fracture transmissivity increases continuously with 2 Geofluids shear displacement before the peak shear strength and is essentially constant after the peak shear strength when the effective normal stress is greater than 10 MPa.…”
Section: Introductionmentioning
confidence: 99%